標準本位政策脈絡下師資培育改革成效之評估：應用「行動模式／改變模式圖式」分析師資培育學程 Effects of Teacher Education Reform in the Standard-Based Policy Context: Analysis of a Teacher Education Program by Applying the Action Model/Change Model Schema - 潘慧玲 Hui-Ling Wendy Pan; 洪秋瑋 Chiu-Wei Hung (National Taiwan Normal University, 2020)
國立臺中教育大學的「教師專業碩士學位學程」可說是臺灣近年來一項重大的師資培育改革方案，其在教育部倡議專業標準本位的脈絡下形成。為瞭解此一變革之成效，以及影響成效的中介機制，本研究以「行動模式／改變模式圖式」作為評鑑取徑。在前置作業中，採取文獻分析、文件分析與訪談方法，建立「教師專業碩士學位學程」之「行動模式／改變模式圖式」，本研究進而採問卷調查與訪談，檢視圖式中「改變模式」三個要素（課程實施、實踐反思、專業表現）之落實情形，以及該學程的課程實施成效（專業表現）受到實踐反思 的中介情形。研究結果顯示，學程之課程實施、師資生之實踐反思與專業表現，均達中高標程度。另課程實施對於實踐反思與專業表現均有直接效果，惟實踐反思中的創新教學，不論對於整體的專業表現或專業表現的構面（專業實踐與專業責任）均產生顯著的部分中介作用；而實踐反思中的觀察反省，則對專業知能產生部分的中介作用。此意謂要造就一位專業表現良好的師資生，除了要有統整的課程設計外，尚須致力於提升師資生創新教學與觀察反省能力，方有助於專業表現效果的強化。上述的研究結果點出創新教學、觀察反省是師培方案要產生預期成果所需的中介機制，而此提供了師資培育改進之重要參考方向。 The Teacher Professional Master Degree Program launched by the National Taichung University of Education has drastically reformed Taiwanese teacher education in recent years. The Ministry of Education promoted this program in a standard-based policy context. To evaluate its effects, this study used the evaluation approach of action model/change model schema. In the preliminary stage, the program's action model/change model schema was constructed through literature analysis, document analysis, and interviews. Furthermore, the survey and interview data were collected to evaluate the schema's change model. Specifically, the implementation of the program and how students' practical reflection mediated the relationship between curriculum implementation and students' professional performance were explored. The findings revealed that the scores of curriculum implementation, students' practical reflection, and professional performance were all at a moderately high level. Additionally, it was found that curriculum implementation exerted main effects on students' practical reflection and professional performance. However, innovative teaching, as a dimension of practical reflection, partially mediated the effects of curriculum implementation either on professional performance or on its two dimensions (professional practice and professional responsibility). Observation and reflection, another dimension of practical reflection, also had mediated effect but only on professional knowledge. The study suggested that integrated curriculum design is crucial for cultivating students' professional competence and that skills of innovative teaching, and observation and reflection strengthen the program's effect on student performance. Those two skills are significant intervening mechanisms that enable teacher education programs to achieve anticipated outcomes, in turn providing a direction for improving teacher education.